Tekniska möjligheter för artificiell spridning av renlav - Krekula, Karl Johan (2007)
Forestry and reindeer husbandry are entitled to use the same land for their operations. For this reason, conflicts occasionally arise between them. Soil scarification is a forestry operation which has a negative effect on the occurrence of reindeer lichen. Reindeer lichens are of crucial importance to reindeers and reindeer husbandry, especially in the winter when reindeers primarily feed on different lichen species (Cladina spp. and Cetraria spp.). Lichens are naturally spread through fragmentation and they are therefore suitable for artificial dispersal in the same manner. However, today there exist no technical system for dispersal of reindeer lichen.